Increase in serum platelet-derived growth factor (PDGF)-BB reflects lymph node involvement in esophageal cancer patients independently from platelet count - Krzystek-Korpacka, M.; Diakowska, D.; Gamian, A.; Matusiewicz, M. (Experimental Oncology, 2011)
Aim: To evaluate clinical significance and diagnostic utility of increase in serum PDGF-BB (sPDGF-BB) in esophageal cancer, which have not been addressed yet despite the relevance of PDGF axis in this cancer type. Methods: Immunoenzymatically assessed sPDGF-BB was related to clinicopathological features, and inflammatory, angiogenic, and lymphangiogenic indices in 84 patients with esophageal cancer and 47 controls. Its diagnostic utility was evaluated by receiver operating characteristics (ROC) curve analysis. Results: sPDGF-BB was significantly higher in esophageal cancer patients than controls (3.76 vs. 2.66 µg/l, p = 0.0001) and corresponded with the disease advancement. Of evaluated clinicopathological features, lymph node metastases and distant metastases were independently associated with an increase in sPDGF-BB; however, only the association with lymph node metastases persist adjustment to platelets. In univariate analysis, sPDGF positively correlated with platelets (r=0.70, p < 0.0001), vascular endothelial growth factor (VEGF)-A (r=0.50, p < 0.0001), VEGF-C (r=0.57, p < 0.0001), white blood cells (r=0.32, p = 0.004), C-reactive protein (r=0.34, p = 0.004), IL-6 (r=0.35, p = 0.003), and IL-8 (r=0.45, p < 0.0001). In multivariate analysis, VEGF-C and platelets were independently associated with sPDGF-BB explaining 61% in its variability. With >2.845 µg/l cut-off, over 76% of patients had elevated sPDGF-BB. Its accuracy as lymph node metastases marker was 75%, sensitivity and specificity corresponding with >3.029 µg/l cut-off were 84 and 61%, respectively. Conclusions: sPDGF-BB owns potential as a possible lymph node metastases marker and might be considered as a diagnostic tool in preliminary evaluation of esophageal cancer patients identifying those likely to be burdened with lymph node metastases, the disease recurrence monitoring, and/or preselecting patients for PDGF-directed cancer therapies.